The Role of Sustainability Reports in Reflecting the Financial Performance of Mining Companies - Sarifah, Putri; Syamsul, Syamsul; Zuhroh, Siti (Lembaga Riset Ilmiah, 2025)
This study investigates the influence of sustainability report disclosures on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Using a quantitative approach with descriptive and verificative methods, the study analyzes 56 observations from 19 companies selected based on specific criteria, including the use of GRI Standards and consistent financial reporting. Sustainability performance is measured through the Sustainability Report Disclosure Index (SRDI), covering economic, environmental, and social dimensions, while financial performance is proxied by Return on Assets (ROA). Data were analyzed using multiple linear regression supported by classical assumption tests. The findings reveal an upward trend in sustainability disclosures across all three dimensions, although with varying consistency among companies. Simultaneous disclosure of the three dimensions does not significantly affect financial performance; however, the social dimension, when examined individually, shows a significant positive impact on ROA. These results highlight the role of social responsibility such as employee welfare and community engagement in enhancing financial outcomes. The study suggests that mining companies improve transparency in sustainability reporting and recommends future research to incorporate additional financial indicators and broader sectors to enrich the analysis.